(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article analyzes the clinical manifestations, risk factors, laboratory and instrumental assessment criteria, primary screening principles, prevention and referral strategies of disorders of physical and sexual development in adolescent girls. Also, data on iron deficiency and iodine deficiency among adolescent girls in the Fergana Valley are discussed from the point of view of the need to adapt diagnostic and preventive approaches to local conditions.